Giorgio del Vecchio e o Direito Natural - Stacchini, Angelo Patrício (2006)
The present work has the objective of studying the Italian Law philosopher Giorgio Del Vecchio s (1878-1970) thought about the Natural Law. The discourse is to verify if Del Vecchio actually defends the existence of Natural Law and, positive the answer, the analysis of jusnaturalism characteristics. Before reaching the work core, a historical-biographical profile of Del Vecchio is introduced, along with an analysis of the general characteristics of his philosophical-juridical thoughts, and their main points. Being certain the influence of Emmanuel Kant over Del Vecchio, the main features of the Kantian Knowledge Theory are presented. From the premise that the jurist s gnosiological position influences his way to conceive and explain the juridical reality, a brief gnosiology analysis is carried out, exposing the main gnosiological chains and the effect on the Philosophy of Law and Jurisprudence. Being this stage overcome, the discourse also contains an overview of the jusnaturalist thought throughout the history, and a presentation of the Natural Law s definition and characteristics. At last, a comparison of Del Vecchio s jusnaturalistic thought and the Natural Law characteristics written on the work is made. In conclusive synthesis, it is stated that Giorgio Del Vecchio accepts the Natural Law, but he does not discharge the Kantian influences of rationalistic bias, which are mainly enlightened in the logical and gnosiological aspects of Del Vecchio s work and in the terminology used by him